2023
DOI: 10.1007/s00702-023-02635-4
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of Parkinson’s disease

Abstract: The heterogeneity of Parkinson’s disease (PD), i.e. the various clinical phenotypes, pathological findings, genetic predispositions and probably also the various implicated pathophysiological pathways pose a major challenge for future research projects and therapeutic trail design. We outline several pathophysiological concepts, pathways and mechanisms, including the presumed roles of α-synuclein misfolding and aggregation, Lewy bodies, oxidative stress, iron and melanin, deficient autophagy processes, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 115 publications
2
16
0
Order By: Relevance
“…Recently, several studies have shown promising results in the diagnosis of PD and MSA using machine learning methods, such as Chen et al (2017), Pang et al (2020), Bu et al (2023), and Chen et al (2023). Among them, the dataset volume used by Pang et al (2020) is comparable to our research, making it highly relevant.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Recently, several studies have shown promising results in the diagnosis of PD and MSA using machine learning methods, such as Chen et al (2017), Pang et al (2020), Bu et al (2023), and Chen et al (2023). Among them, the dataset volume used by Pang et al (2020) is comparable to our research, making it highly relevant.…”
Section: Discussionmentioning
confidence: 59%
“…This poses a great challenge for doctors in their diagnosis ( Song et al, 2007 ; Antonini, 2010 ). Parkinson’s disease has a high degree of heterogeneity, with different clinical subtypes, which makes diagnosis difficult ( Wullner et al, 2023 ). According to statistics, the misdiagnosis rate of early-stage Parkinson’s disease can be as high as 20–30% ( Poewe and Wenning, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PD is characterized by these pathological hallmarks, there is a remarkable heterogeneity in the aetiology and pathogenesis of the disorder [ 5 , 9 ]. The hetereogeneity can manifest as variation in age of onset, disease progression, clinical phenotypes, cellular pathways, neurotransmitter systems, epigenetics and underlying genetic risks [ 10 , 11 ].…”
Section: Parkinson's Disease—a Complex and Heterogeneous Disordermentioning
confidence: 99%
“…Indeed, a-synuclein is normally a presynaptic cytosolic monomer but can undergo oligomerization and brillation contributing to synucleopathies (Stefanis 2012;Bendor et al 2013;Goedert, 2001;Gallardo et al, 2020). Competing theories suggest that a-syn may rst begin to misfold and aggregate in either the periphery and/or in the anterior olfactory region of the brain before eventually reaching the midbrain dopaminergic system (Braak et al, 2003;Wüllner et al, 2023;Borghammer et al, 2022). Aggregation and spread of a-synuclein can be affected by several missense mutations, including A30P, E46K, H50Q and A53T (Burré et al, 2018), with the A53T mutation being particularly involved in the acceleration of brilization (Tofaris & Spillantini, 2007;Teravskis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%